Attitudes of Pediatricians to ADHD Diagnosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Pediatricians' perceptions of ADD and ADHD diagnosis, child and family communication concerning diagnosis and treatment, and treatment issues were examined in a cross-sectional survey involving 380 members of the American Academy of Pediatrics and conducted by the Department of Psychology, University of California-Riverside and Loma Linda University Medical Center, CA.